Between the Guerrillas and the State : The Cocalero Movement, Citizenship, and Identity in the Colombian Amazon - Ramírez, María Clemencia (Book collections on Project MUSE., 2011)
Uses 1996 strike by Colombian coca workers as site to study the state and social movements, analyzing how peasants denied full citizenship become political players in a way that defines the Colombian state in the international arena.